(untitled) - Kuratko, Donald F. (Mason, Ohio, 2004)
Part 1 Entrepreneurship in the Twenty-First Century 1; Part 2 The Entrepreneurial Perspective 110;..
Keywords: Entrepreneurship,Doanh nhân; United States,Hoa Kỳ